RETURNING GENETIC RESEARCH RESULTS TO INDIVIDUALS: POINTS-TO-CONSIDER - Renegar, Gaile (Bioethics, 2006)
This paper is intended to stimulate debate amongst stakeholders in the international research community on the topic of returning individual genetic research results to study participants. Pharmacogenetics and disease genetics studies are becoming increasingly prevalent, leading to a growing body of information on genetic associations for drug responsiveness and disease susceptibility with the potential to improve health care. Much of these data are presently characterized as exploratory (non-validated or hypothesis-generating). There is, however, a trend for research participants to be permitted access to their personal data if they so choose. Researchers, sponsors, patient advocacy groups, ethics committees and regulatory authorities are consequently confronting the issue of whether, and how, study participants might receive their individual results. Noted international ethico-legal guidelines and public policy positions in Europe and the United States are reviewed for background. The authors offer ‘Points-to-Consider’ regarding returning research results in the context of drug development trials based on their knowledge and experience. These considerations include: the clinical relevance of data, laboratory qualifications, informed consent procedures, confidentiality of medical information and the competency of persons providing results to participants. The discussion is framed as a benefit-to-risk assessment to balance the potential positive versus negative consequences to participants, while maintaining the integrity and feasibility of conducting genetic research studies.